2005
DOI: 10.4049/jimmunol.174.12.8082
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Role of Phosphodiesterase 4 in Lipopolysaccharide-Stimulated Prostaglandin E2 Production and Matrix Metalloproteinase-9 Activity in Human Amniochorionic Membranes

Abstract: Chorioamniotic infection is a leading cause of preterm premature rupture of fetal membranes (amnion and chorion). Bacterial infection induces an inflammatory response characterized by elevated production of proinflammatory cytokines; the latter activate the production of both PGs that stimulate uterine contractions, and matrix metalloproteinases (MMPs) that degrade the extracellular matrix of the chorioamniotic membranes. The inflammatory response is under the control of cAMP content, which is partly regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…We showed previously in humans that PDE4 inhibition blocks spontaneous contractions of myometrial strips. It also abolished the activation in fetal membranes of metalloproteases and prostaglandin syntheses that may lead to preterm premature rupture of the membranes (41)(42)(43). Here, we report that PDE4 inhibition blocks intrauterine inflammation, which may injure the fetus if uncontrolled.…”
Section: Discussionmentioning
confidence: 85%
“…We showed previously in humans that PDE4 inhibition blocks spontaneous contractions of myometrial strips. It also abolished the activation in fetal membranes of metalloproteases and prostaglandin syntheses that may lead to preterm premature rupture of the membranes (41)(42)(43). Here, we report that PDE4 inhibition blocks intrauterine inflammation, which may injure the fetus if uncontrolled.…”
Section: Discussionmentioning
confidence: 85%
“…Our previous works showed that PDE4 inhibition is not only able to abolish metalloprotease activation and prostaglandin synthesis in fetal membranes but is also able to block spontaneous contractions of myometrial strips (21,40). Given its dual myorelaxant and anti-inflammatory properties (41), selective PDE4 inhibition may represent a novel approach in the management of inflammation-induced preterm delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent intrauterine inflammation was concomitant with nuclear localization of NF-B in a specific set of murine cells at the vicinity of maternal cells and PDE4 inhibition prevented the NF-B nuclear translocation. Furthermore, we evidenced in a previous study that PDE4 was the main PDE family expressed in human fetal membranes, and PDE4 activity was increased by LPS (21). PDE4 inhibitors blocked the release of proinflammatory cytokines, prostaglandins, and metalloproteases induced by LPS in these membranes.…”
mentioning
confidence: 99%
“…The proteolytic activity of pro-MMP-9 secreted into the culture medium was assessed by gelatin zymography on 10% SDS gel incorporating 1 mg/ ml gelatin as previously described (25). Briefly, 3 mg protein was loaded and subjected to electrophoresis under nonreducing conditions.…”
Section: Zymographymentioning
confidence: 99%